The Practicalities and Perils of Ambulatory Assessment's Promise: Introduction to a Special Section. (1st October 2019) - Modecki, Kathryn Lynn; Goldberg, Rachel E.; Ehrenreich, Samuel E.; Russell, Michael; Bellmore, Amy
Abstract : Ambulatory assessment (AA) offers one of the most exciting approaches for opening the dynamic "black box" of adolescents' daily lives. In this introduction, we spotlight AA's surprisingly restricted market share within adolescent scholarship. We describe thorny challenges these intense methods can pose when conducting adolescent research "in situ" and underscore that capturing quality AA data means placing adolescents' developmental stage at the forefront. The novel research reported in this special section speaks to these challenges and underscores the promise of AA for conducting developmentally salient science. The nine articles included in the section span multiple disciplines (Sociology, Psychology, Public Health) and reflect diverse viewpoints, approaches, and theories. All provide multiple novel best‐practice strategies for conducting AA scholarship with adolescents.